The overall funding outlook - Bee Boileau; David Phillips (Institute for Fiscal Studies (IFS), 2023)
The Scottish Government's overall budget depends both on funding from the UK government, which is determined largely via the Barnett formula, and on its own devolved revenues, borrowing and reserves, which are governed by the Fiscal Framework. This chapter of the report looks at the funding outlook in the short term (2022-23 and 2023-24), medium term (2024-25 to 2027-28) and beyond, drawing on Scottish Government and Scottish Fiscal Commission (SFC) figures.
Keywords: 330; Government finances and spending; Scottish Budget 2023-24; Devolved government finances; Government spending; Scottish independence; Fiscal rules and frameworks